1984
DOI: 10.1128/aem.48.1.73-77.1984
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chlorination on antibiotic resistance profiles of sewage-related bacteria

Abstract: A total of 1,900 lactose-fermenting bacteria were isolated from raw sewage influent and chlorinated sewage effluent from a sewage treatment plant, as well as from chlorinated and neutralized dilute sewage, before and after a 24-h regrowth period in the laboratory. Of these isolates, 84% were resistant to one or more antibiotics. Chlorination of influent resulted in an increase in the proportion of bacteria resistant to ampicillin and cephalothin, the increase being most marked after regrowth occurred following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(36 citation statements)
references
References 22 publications
(18 reference statements)
0
34
0
Order By: Relevance
“…Of possible significance are the findings of Armstrong et al (1981Armstrong et al ( , 1982 who isolated multiple-antibiotic-resistant bacteria from drinking water, especially in view of the subsequent proposal (Murray et al 1984) that disinfection and purification of water may augment the occurrence of antibiotic-resistant bacteria. Chlorination was suggested as being responsible for selecting or inducing such changes.…”
Section: Biocide Usage and Antibiotic Resistance In Gram-negative Bacmentioning
confidence: 99%
“…Of possible significance are the findings of Armstrong et al (1981Armstrong et al ( , 1982 who isolated multiple-antibiotic-resistant bacteria from drinking water, especially in view of the subsequent proposal (Murray et al 1984) that disinfection and purification of water may augment the occurrence of antibiotic-resistant bacteria. Chlorination was suggested as being responsible for selecting or inducing such changes.…”
Section: Biocide Usage and Antibiotic Resistance In Gram-negative Bacmentioning
confidence: 99%
“…Previous studies have found evidence that chlorination of wastewater selects for multiple antibiotic-resistant bacteria, but with mixed results. Murray et al (1984) found that regrowth bacteria had a higher resistance to ampicillin (83%), cephalothin (75%), and tetracycline (18%), but a decreased resistance to kanamycin (2%). In another study, Staley et al (1988) found that chlorinated fecal-coliform isolates were more sensitive to kanamycin, streptomycin, and tetracycline, but more resistant to ampicillin.…”
Section: Discussionmentioning
confidence: 99%
“…Also, fecal coliforms have been shown to survive and regrow in wastewater effluent following chlorination (Heukelekian, 1951;Shuval et al, 1973). Some researchers have shown that regrowth bacterial populations consisted of a higher proportion of multiple antibiotic resistant (MAR) bacteria than the initial surviving population in chlorinated effluent (Murray et al, 1984;Rusin, 1989). Therefore, the microbial removal capability of these wetland systems may not be realized, resulting in counts exceeding acceptable levels for regulatory permitting.…”
Section: Introductionmentioning
confidence: 99%
“…The likelihood is further reduced by the fact that these agents are unstable or volatile and thus, do not persist in the environment in an active form. It is therefore perhaps surprising that Murray et al (1984) reported that chlorination of sewage produced an increase in the proportion of antibiotic-resistant isolates. A suggested explanation was that chlorination caused selection of stress-tolerant strains which were also antibiotic-resistant, or stimulated transfer of resistance plasmids, but these aspects were not investigated.…”
Section: 24mentioning
confidence: 99%